Geographical epidemiology of health and overall deprivation in England, its changes and persistence from 2004 to 2015: a longitudinal spatial population study. Issue 2 (20th December 2017) - Kontopantelis, Evangelos; Mamas, Mamas A; van Marwijk, Harm; Ryan, Andrew M; Buchan, Iain E; Ashcroft, Darren M; Doran, Tim
Abstract : Background: Socioeconomic deprivation is a key determinant for health. In England, the Index of Multiple Deprivation (IMD) is a widely used composite measure of deprivation. However, little is known about its spatial clustering or persistence across time. Methods: Data for overall IMD and its health domain were analysed for 2004–2015 at a low geographical area (average of 1500 people). Levels and temporal changes were spatially visualised for the whole of England and its 10 administrative regions. Spatial clustering was quantified using Moran's I, correlations over time were quantified using Pearson's r. Results: Between 2004 and 2015 we observed a strong persistence for both overall (r=0.94) and health-related deprivation (r=0.92). At the regional level, small changes were observed over time, but with areas slowly regressing towards the mean. However, for the North East, North West and Yorkshire, where health-related deprivation was the highest, the decreasing trend in health-related deprivation reversed and we noticed increases in 2015. Results did not support our hypothesis of increasing spatial clustering over time. However, marked regional variability was observed in both aggregate deprivation outcomes. The lowest autocorrelation was seen in the North East and changed very little over time, while the South East had the highest autocorrelation at all time points. Conclusions: Overall and health-related deprivation patterns persisted in England, with large and unchanging health inequalities between the North and the South. The spatial aspect of deprivation can inform the targeting of health and social care interventions, particularly in areas with high levels of deprivation clustering.